Effect of saroglitazar in South Indian patients with diabetic dyslipidemia uncontrolled on a moderate-intensity statin and the association of PPAR α and γ gene polymorphisms with its response - Bage, Isaac J.; Kamalanathan, Sadishkumar; Selvarajan, Sandhiya; Sahoo, Jayaprakash; Mathaiyan, Jayanthi; Naik, Dukhabandhu (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Diabetic dyslipidemia is associated with atherosclerosis risk factors and cardiovascular disease. Saroglitazar is a dual PPAR α and γ agonist approved initially for diabetic dyslipidemia and later for managing non-alcoholic steatohepatitis and hyperglycemia in T2DM. This study was conducted to estimate the association of studied PPAR α and γ gene polymorphisms among patients with diabetic dyslipidemia at baseline and with triglyceride response to saroglitazar administration. Methods: A total of 54 diabetic dyslipidemia patients who are not controlled i.e., triglycerides (TG)>200 mg/dl with moderate intensity of atorvastatin (≥10 mg) were recruited to the study. All the patients were given saroglitazar 4 mg once daily for 12 weeks. PPARα single nucleotide polymorphisms (SNPs) rs1800206, rs4253778, rs135542 and those of PPARγ gene rs3856806, rs10865710, rs1805192 were genotyped by real-time PCR. Results: 54 patients (67% female) with a mean age of 48.01±6.73 years were given saroglitazar 4 mg once daily for 12 weeks. There was a significant decrease in TG (36.9%) from baseline of 292.33±83.81mg/dl (mean±SD) to 184.46±95.90 mg/dl (<0.001) and in HbA1c (0.66%) from baseline of 8.5% to 7.8% (<0.001). PPAR α and PPAR γ gene variants did not show any association with TG lowering response. Conclusions: Saroglitazar 4mg once daily effectively decreases the TG, non-HDL-C levels, and HbA1c with no major adverse events, and TG lowering response is not associated with the studied polymorphisms.